Los estilos de crianza y su relación con la convivencia en niños de 2 a 3 años del centro de educación inicial particular san Gabriel de la ciudad de Loja, periodo académico 2018 – 2019 - Gonzalez Guaman, Marjorie Guissella (2020)
The research entitled THE STYLES OF BREEDING AND ITS RELATION TO COEXISTENCE IN CHILDREN FROM 2 TO 3 YEARS OLD FROM THE SAN GABRIEL DE LA CIUDAD DE CIUDAD DE LOJA CITY, ACADEMIC PERIOD 2018 - 2019 had the general objective of identifying parenting styles and their relationship with coexistence in children from 2 to 3 years old; the methods were used: scientific, descriptive, analytical-synthetic and inductive-deductive; The instruments applied were: the Scale of Norms and Requirements (ENE) for 11 parents and the observation sheet for 11 children. With the initial evaluation of the ENE scale, 55% of parents who exercised a style of permissive upbringing, 27% authoritarian and 18% democratic; and with the observation guide it was obtained that 41% of children were in the beginning, 53% in the process and 6% in acquired; the alternative proposal “Learning with the family” aimed at parents and “From your hand I learn, play and live happily” aimed at children were planned and executed, which reflected favorable changes in the results; In the final evaluation, it was found that 73% of parents improved their parenting style, placing themselves in the democratic style, 18% in authoritarian and 9% in permissive; On the other hand, it was found that 73% of the children acquired the skills, 27% are still in process, totally decreasing the percentage at the beginning; With these results it is concluded that parenting styles are related to coexistence, so it is recommended that teachers give workshops and activities aimed at achieving a good parenting style and harmonious coexistence.